Two Phase 1, Randomized, Double-Blind, Placebo-Controlled, Single-Ascending-Dose Studies To Investigate the Safety, Tolerability, and Pharmacokinetics of an Anti-Influenza A Virus Monoclonal Antibody, MHAA4549A, in Healthy Volunteers - Lim, Jeremy J.; Deng, Rong; Derby, Michael A.; Larouche, Richard; Horn, Priscilla; Anderson, Malia; Maia, Mauricio; Carrier, Stephanie; Pelletier, Isabelle; Burgess, Tracy; Kulkarni, Priya; Newton, Elizabeth; et al. (Antimicrobial agents and chemotherapy, 2016)
Hospitalized patients with severe influenza are at significant risk for morbidity and mortality. MHAA4549A is a human monoclonal immunoglobulin (Ig) G1 antibody that binds to a highly conserved stalk region of the influenza A virus hemagglutinin protein and neutralizes all tested seasonal human influenza A virus strains. Two phase 1 trials examined the safety, tolerability, and pharmacokinetics of MHAA4549A in healthy volunteers. Both single ascending-dose trials were randomized, double blinded, and placebo controlled. Trial 1 randomized 21 healthy adults into four cohorts receiving a single intravenous dose of 1.5, 5, 15, or 45 mg/kg MHAA4549A or placebo. Trial 2 randomized 14 healthy adults into two cohorts receiving a single intravenous fixed dose of 8,400 mg or 10,800 mg of MHAA4549A or placebo. Subjects were followed for 120 days after dosing. No subject was discontinued in either trial, and no serious adverse events were reported. The most common adverse event in both studies was mild headache (trial 1, 4/16 subjects receiving MHAA4549A and 1/5 receiving placebo; trial 2, 4/8 subjects receiving MHAA4549A and 2/6 receiving placebo). MHAA4549A produced no relevant time- or dose-related changes in laboratory values or vital signs compared to those with placebo. No subjects developed an antitherapeutic antibody response following MHAA4549A administration. MHAA4549A showed linear serum pharmacokinetics, with a mean half-life of 22.5 to 23.7 days. MHAA4549A is safe and well tolerated in healthy volunteers up to a single intravenous dose of 10,800 mg and demonstrates linear serum pharmacokinetics consistent with those of a human IgG1 antibody lacking known endogenous targets in humans. (These trials have been registered at ClinicalTrials.gov under registration no. NCT01877785 and NCT02284607).